Dietary fatty acid oxidation is decreased in non‐alcoholic fatty liver disease: A palmitate breath test study. (15th December 2019) - Naguib, Gihan; Morris, Nevitt; Yang, Shanna; Fryzek, Nancy; Haynes‐Williams, Vanessa; Huang, Wen‐Chun A.; Norman‐Wheeler, Jaha; Rotman, Yaron
Abstract: Background & Aim: Hepatic fat excess in non‐alcoholic fatty liver disease (NAFLD) reflects an imbalance between fat accumulation and disposal. Conflicting data exist for the role of fatty acid oxidation (FAO), one of the disposal pathways, and have mostly come from the studies delivering fatty acids (FAs) intravenously. Whether FAO of orally provided FAs is affected in NAFLD is unknown. Methods: We performed a breath test study to measure FAO in subjects with NAFLD and healthy controls. Subjects ingested [1‐ 13 C] palmitic acid (PA, 10 mg/kg) in a liquid meal and the rate of 13 CO2 appearance in expired air was measured over 6 hours by a BreathID device (Exalenz) to obtain the cumulative percent dose recovered (CPDR), the total amount of ingested 13 C recovered. CPDR was corrected by the results of a [1‐ 13 C] acetate breath test, performed 1‐4 weeks later, to calculate the rate of PA β‐oxidation. Results: Palmitic acid oxidation was 27% lower in 43 subjects with NAFLD compared to 11 controls (CPDR 9.5 ± 2.4% vs 13.1 ± 3.7%, P = .0001) and this persisted after correcting for acetate (29.3 ± 10.5 vs 36.6 ± 13.9, P = .03). The decrease in FAO was not because of the delayed transit as the time to peak 13 C detection did not differ between groups (4.9 ± 1.2 hours vs 4.7 ± 0.8 hours, P = .7). Rates of PA oxidation were not correlated with obesity, hepatic or adipose insulin resistance, alanine aminotransferase, liver fat content and NAFLD histology. Conclusion: Fatty acid oxidation of orally delivered FA is decreased in NAFLD compared to healthy controls, likely reflecting decreased β‐oxidation. The use of a breath test offers non‐invasive dynamic assessment of FAO.